2020
DOI: 10.1186/s12957-020-02100-6
|View full text |Cite
|
Sign up to set email alerts
|

Is left-sided involvement of hepatocellular carcinoma an important preoperative predictive factor of poor outcome?

Abstract: Background The tumor location is the most simple clinical factor and important in liver surgery to make surgical procedure. However, no previous study has investigated the prognostic differences and clinical features of hepatocellular carcinoma showing specific laterality. This study is the first report to focus on the laterality and aimed to lead to more simple and useful predictive factor rather than recent complicated predictive models. Methods Patients who underwent liver resection for the first time for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Although patients could get an early diagnosis combined with comprehensive treatment nowadays, due to the tumor’s malignant character, the prognosis of liver cancer remains unsatisfactory [ 3 , 4 ]. Factors such as age, tumor size and tumor number, pathologic TNM stage, and vascular invasion have been identified as factors influencing the prognosis of liver cancer patients [ 5 7 ]. Several researchers have found that overweight status increases the risk of hepatocellular carcinoma (HCC) by 17%, and obese status increases the risk of HCC by 90% compared with normal-weight individuals [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although patients could get an early diagnosis combined with comprehensive treatment nowadays, due to the tumor’s malignant character, the prognosis of liver cancer remains unsatisfactory [ 3 , 4 ]. Factors such as age, tumor size and tumor number, pathologic TNM stage, and vascular invasion have been identified as factors influencing the prognosis of liver cancer patients [ 5 7 ]. Several researchers have found that overweight status increases the risk of hepatocellular carcinoma (HCC) by 17%, and obese status increases the risk of HCC by 90% compared with normal-weight individuals [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that GVI is one of significant prognostic factors for patients with HCC [ 27 ]. A recent study with a relatively large cohort sample analyzed the preoperative factors associated with a survival rate of more than 2 years after SR for HCC with GVI [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, we could reliantly deduce that the negative prognostic effect of mGVI would diminish after 1 year in the postoperative period. It has been reported that GVI is one of significant prognostic factors for patients with HCC [27]. A recent study with a relatively large cohort sample analyzed the preoperative factors associated with a survival rate of more than 2 years after SR for HCC with GVI [28].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no study to date has evaluated the clinical outcomes of HCC patients in relation to the disease site to be treated with Y90-RE. In the surgical literature, however, left hepatic lobe HCC disease has been associated with worse clinical outcomes after surgical intervention [46], suspected to be driven in part by the greater difficulty in attaining negative surgical margins.…”
Section: Discussionmentioning
confidence: 99%